Chromatic Classes of 2-Connected (n, n+4)-Graphs with Exactly Three Triangles and at Least Two Induced 4-Cycles. (2nd November 2011) - Lau Lau, G. C. G. C.; Peng Peng, Y. H. Y. H.
Abstract : For a graph G, let P ( G, λ ) be its chromatic polynomial. Two graphs G and H are chromatically equivalent, denoted G H, if P ( G, λ ) = P ( H, λ ) . A graph G is chromatically unique if P ( H, λ ) = P ( G, λ ) implies that H ≅ G . In this paper, we determine all chromatic equivalence classes of 2-connected (n, n + 4 )-graphs with exactly three triangles and at least two induced 4-cycles. As a byproduct of these, we obtain various new families of χ -equivalent graphs and χ -unique graphs.